DR.MAHATHIR MOHAMAD'S RHETORICAL APPEALS IN SPEECHES ON HUMANITARIAN THEMES - Sheela Faizura, Nik Fauzi; Su Hie, Ting (The Muallim Journal of Social Sciences and Humanities (MJSSH), 2025)
This study examined how Dr. Mahathir Mohamad employed Aristotelian rhetorical appeals and sub themes in six speeches on humanitarian theme during his second term as Prime Minister of Malaysia. Employing Braun and Clarke’s (2008) thematic analysis, findings reveal a dominant reliance on pathos (61.81%) over logos (27.45%) and ethos (10.74%) which highlight Dr. Mahathir’s strategic use of emotional engagement to mobilize empathy for pressing humanitarian issues such as refugee crises, global solidarity, and environmental justice. Three overarching themes emerge which are critique of Western hegemony, Malaysia’s distinct approach vis-à-vis Western powers, and calls for an equitable international framework. The sub themes reflect how rhetorical strategies can shape discourses on global crises. These results contribute to the broader scholarship on political rhetoric by illustrating how emotion-driven appeals and nationalist positioning can influence policy debates and galvanize international support. Practically, they suggest that leaders seeking to promote humanitarian reforms might prioritize emotive rhetoric and culturally resonant themes to strengthen calls for fairer global governance. Future research could expand this analysis to a wider range of Dr. Mahathir’s speeches and compare them across different political contexts to refine understanding of how rhetorical approaches evolve in response to shifting global humanitarian challenges.